Preoperative hair removal and surgical site infections: network meta-analysis of randomized controlled trials. Issue 2 (October 2015) - Lefebvre, A.; Saliou, P.; Lucet, J.C.; Mimoz, O.; Keita-Perse, O.; Grandbastien, B.; Bruyère, F.; Boisrenoult, P.; Lepelletier, D.; Aho-Glélé, L.S.; French study group for the preoperative prevention of surgical site infections, †
Summary Preoperative hair removal has been used to prevent surgical site infections (SSIs) or to prevent hair from interfering with the incision site. We aimed to update the meta-analysis of published randomized controlled trials about hair removal for the prevention of SSIs, and conduct network meta-analyses to combine direct and indirect evidence and to compare chemical depilation with clipping. The PubMed, ScienceDirect and Cochrane databases were searched for randomized controlled trials analysing different hair removal techniques and no hair removal in similar groups. Paired and network meta-analyses were conducted. Two readers independently assessed the study limitations for each selected article according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method. Nineteen studies met the inclusion criteria. No study compared clipping with chemical depilation. Network meta-analyses with shaving as the reference showed significantly fewer SSIs with clipping, chemical depilation, or no depilation [relative risk 0.55, 95% confidence interval 0.38–0.79; 0.60, 0.36–0.97; and 0.56, 0.34–0.96, respectively]. No significant difference was observed between the absence of depilation and chemical depilation or clipping (1.05, 0.55–2.00; 0.97, 0.51–1.82, respectively] or between chemical depilation and clipping (1.09, 0.59–2.01). This meta-analysis of 19 randomized controlled trials confirmed the absence of any benefit of depilation to prevent surgical site infection, and the higher risk of surgical site infection when shaving is used for depilation. Chemical depilation and clipping were compared for the first time. The risk of SSI seems to be similar with both methods.